A randomised crossover study to compare the user seal check and quantitative fit test between two types of duckbill N95 particulate respirator masks: The Halyard Fluidshield® N95 and the BSN Medical ProShield® N-95 particulate respirator masks. Issue 2 (March 2021) - Williams, Daryl L; Kave, Benjamin; Lee, Keat; Segal, Reny; Krieser, Roni B; Mezzavia, Paul M; Ng, Irene
N95 particulate respirator masks are currently recommended for all healthcare workers who care for patients with suspected or confirmed coronavirus disease (COVID-19) when performing aerosol-generating procedures. The protection provided by N95 particulate respirator masks is dependent on the filter's efficiency and seal quality. In this prospective randomised crossover study, we conducted the user seal check and the quantitative fit test on two readily available duckbill models of N95 masks, the Halyard Fluidshield® N95 (Halyard, Alpharetta, GA, USA) and the BSN Medical ProShield® N-95 (BSN Medical, Mount Waverley, Victoria) particulate respirator masks. We recruited a total of 96 anaesthetic staff, of whom 26% were of South-East Asian ethnicity. We found that both types of masks provided reasonably high fit test pass rates among our participants and there was no significant difference between the two brands (77% for the Fluidshield and 65% for the ProShield, P  = 0.916). Ninety-two percent of the participants could find at least one well-fitted mask among these two types of masks. We also demonstrated that the user seal check had low accuracy and low concordance (kappa coefficient of 0.16 for the Fluidshield and 0.08 for the ProShield) when compared to the quantitative fit test, and hence was not a reliable method to test seal quality.